(5x+4)=(8x-3)

Simple and best practice solution for (5x+4)=(8x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+4)=(8x-3) equation:


Simplifying
(5x + 4) = (8x + -3)

Reorder the terms:
(4 + 5x) = (8x + -3)

Remove parenthesis around (4 + 5x)
4 + 5x = (8x + -3)

Reorder the terms:
4 + 5x = (-3 + 8x)

Remove parenthesis around (-3 + 8x)
4 + 5x = -3 + 8x

Solving
4 + 5x = -3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
4 + 5x + -8x = -3 + 8x + -8x

Combine like terms: 5x + -8x = -3x
4 + -3x = -3 + 8x + -8x

Combine like terms: 8x + -8x = 0
4 + -3x = -3 + 0
4 + -3x = -3

Add '-4' to each side of the equation.
4 + -4 + -3x = -3 + -4

Combine like terms: 4 + -4 = 0
0 + -3x = -3 + -4
-3x = -3 + -4

Combine like terms: -3 + -4 = -7
-3x = -7

Divide each side by '-3'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| -14u+2u+16u=-12 | | 2(-2x-y)=2(1) | | y^4-36y^2=-35 | | 2x+3(3x-4)=21 | | -2p+5p=3-21 | | X(2x-4)=(2x+8)(x-8) | | 56t^2-23t-63=0 | | 5(4-x)=-10 | | s^3+16s^2+64s=0 | | 6x^2+35x+25= | | 3x(a-3)-5(3-a)=0 | | 7x+3=-36 | | (x)(3x-y)(4x+5y)= | | 3x+7=-36 | | 8x-5=7-4x | | x/3-4=7 | | x(3x-y)(4x+5y)= | | -17+11+6=7t | | 2x+8=-48 | | 7xy^4-7xy^2=0 | | 3n^2-3n-36=0 | | 5(5x+3)=3(8x-2+4) | | x(3x-y)(4x+5x)= | | -7+11+6=7t | | 2x+25=-2x-7 | | 6(x-2)=14 | | 3x-39=75 | | 5=7t | | -4x+(-2x+6)=9 | | 13x+23=2x-13 | | -3x-8=x+16 | | -6x+2(x+6)=42 |

Equations solver categories